Redesain Pasar Induk Cibitung Dengan Konsep Arsitektur Hybrid - Retno Fitri Astuti; Feny Ida Pratiwi (Prosiding Sains dan Teknologi, 2022)
Bekasi Regency has Cibitung Main Market as a distribution center largest fruit and vegetable market and this is a source of Original Income Region (PAD) for the surrounding community, especially the Cibitung area. Though has great potential, Cibitung Main Market also has problems, Among them is the circulation of a humid market space that has the potential to accelerate decay, the kiosk building is old and is only occupied by 30% of traders only, the lack of water absorption, the irregular parking area accumulates garbage the rest of the vegetables and fruit make the drains clogged into puddles until they flood in the market area. Redesign or rearrangement and redesign with the concept Architecture Hybrid is needed to overcome these problems, the goal is to change people's view of the people's market from a slum, smelly, dirty view to a comfortable people's market for selling and shopping. Keywords: Redesign, Cibitung Main Market, Problems, Hybrid Architecture.